Penerapan Produksi Bersih untuk Meningkatkan Efisiensi Proses Pelapisan Logam - Amelia Theresia Sirait; Erliza Noor; Andes Ismayana (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Metal coating wastes generally bring about environmental health problems resulting from liquid wastes that contain heavy metals. The waste processing carried out thus far does not solve the problems because it just move wastes to other media. Cleaner production comes to be an alternative in minimizing liquid wastes, for water consumption, and for raw material. The present research was intended to identify wastewater resulting from the production stage, get cleaner production opportunities that can be applied, and give priority to clean production opportunities. The research stages began with a quick scan to identify the sources of wastes in production process and to determine an alternative of cleaner production chance, and then an economic computation was done, including B/C ratio and payback period. The determination of the priority of cleaner production technique given to a company was conducted by using exponential comparison method. The results showed that liquid wastes were originated from the process of fat removing, metal coating and process of cleaning up the remaining oxides. Liquid waste or loss in the form of contaminated fat solvents, the quite great loss of water due to evaporation and leakage. Cleaner production opportunities that can be applied by modifying/adding tools so as to prevent alkali solutionfrom being contaminated, reducing evaporation and reducing leakages by good housekepping. Three opportunities for cleaner production obtained to have B/C Ratio of more than 1 is can be implemented. Based on the exponential comparison method, the main priority of cleaner production is found, that is pipe changes in the residual oxide cleaning process to avoid leakage, technically and operationally the easiest to implement and followed successively with modifiying/adding tools to process of fat removing and metal coating.